Pineapple pests and diseases in the Lesser Antilles : survey results & recommendations - Marie, Franck (IICA Port of SpainTT, 1995)
Presents the results of a survey for each country visited. Provides information and recommendations for crop protection for the main pineapple pests and diseases identified during the survey.